1996
DOI: 10.1073/pnas.93.9.4040
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 3 or interleukin 1 abrogates the reconstituting ability of hematopoietic stem cells.

Abstract: Because of their known myelopoietic activities, both interleukin (IL)-3 and IL-1 are often used in combination with other cytokines for in vitro (ex vivo) expansion of stem cells. We have investigated the effects of IL-3 and IL-1 on in vitro expansion of murine hematopoietic stem cells with long-term engraftment capabilities, using a highly purified progenitor population. Lineage-negative, Ly-6A/E+, c-kit+ bone marrow cells from male mice were cultured in suspension in the presence of stem cell factor, IL-6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
2
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(102 citation statements)
references
References 27 publications
(5 reference statements)
8
91
2
1
Order By: Relevance
“…Protein-protein interactions involving the rhd and ETS proteins, C/EBP, or CBFb are not shown ALL with a t(5;14) abnormality remains the only ALL identi®ed thus far that expresses IL-3 (Grimaldi and Meeker, 1989;Meeker et al, 1990). Although IL-3 has been shown to have an inhibitory role on the growth of B cells under certain in vitro conditions (Yonemura et al, 1996), we have no evidence that repression of IL-3 expression by TEL-AML1 in B cells could have functional consequences.…”
Section: Discussioncontrasting
confidence: 59%
“…Protein-protein interactions involving the rhd and ETS proteins, C/EBP, or CBFb are not shown ALL with a t(5;14) abnormality remains the only ALL identi®ed thus far that expresses IL-3 (Grimaldi and Meeker, 1989;Meeker et al, 1990). Although IL-3 has been shown to have an inhibitory role on the growth of B cells under certain in vitro conditions (Yonemura et al, 1996), we have no evidence that repression of IL-3 expression by TEL-AML1 in B cells could have functional consequences.…”
Section: Discussioncontrasting
confidence: 59%
“…These cells tend to differentiate in tissue cultures supplemented with growth factors, thereby reducing their capacity to repopulate bone marrow and radioprotect recipient mice. 39,40 Growth factors are required to stimulate cell division in culture, which is a prerequisite for integration of retroviral sequences into the genome. In the present study, we found a total culture period of 6 days suitable while prolongation to 8 days resulted in engraftment failure.…”
Section: Then Spun Down and Resuspended In Medium With Or Without Vermentioning
confidence: 99%
“…The negative effect of IL3 for LTC-IC amplification could be attributed to an increased induction of proliferation and maturation of primitive stem cells at the expense of the self-renewal capacity, as recently demonstrated. [19][20][21] The experiments described here throw new light on the kinetics of expansion of primitive stem cells. Indeed, data reported so far on LTC-IC amplification are limited to incubation periods of a few weeks.…”
Section: Figurementioning
confidence: 99%